2018
DOI: 10.23893/1307-2080.aps.05627
|View full text |Cite
|
Sign up to set email alerts
|

Flurbiprofen loaded gel based topical delivery system: formulation and in vitro characterization with new developed uplc method

Abstract: Objective: The purpose of this study was to formulate flurbiprofen (FLB) loaded methylcellulose (MC), hydroxypropyl methylcellulose (HPMC) and Carbopol®940 (C-940) based gel formulations with the help of dispersion method for topical application. Additionally, in this study also a new ultra performance liquid chromatography method was developed for the determination of FLB, which was not previously entered into the literature.Method: FLB loaded gel formulations with the help of dispersion method for topical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Range is the interval between the upper and lower concentration of active agent that have been indicated to be determined with precision, accuracy and linearity using the method as written. The accuracy and precision of the method are within the acceptable range [15]. In this study the range was observed linearly to the highest concentration (220 μg.mL -1 , R 2 :0.9999).…”
Section: Methods Validationsupporting
confidence: 61%
See 3 more Smart Citations
“…Range is the interval between the upper and lower concentration of active agent that have been indicated to be determined with precision, accuracy and linearity using the method as written. The accuracy and precision of the method are within the acceptable range [15]. In this study the range was observed linearly to the highest concentration (220 μg.mL -1 , R 2 :0.9999).…”
Section: Methods Validationsupporting
confidence: 61%
“…RSD % for retention time for six different conditions were between 0.18 and 0.64 % (Table 3), which is well inside the proposed acceptance basis of ≤5 %. RSD % for area response was from 0.15 to 0.87 %, which also passed the proposed acceptance basis of ≤2 % [15]. Therefore, it can be concluded that the method is consistent in front of the wavelength, temperature and flow rate.…”
Section: Methods Validationmentioning
confidence: 51%
See 2 more Smart Citations
“…Conclusively, procedure proposed in this study can be used for routine, simultaneous and concurrent CVL determination. This stability indicating method can be adaptable for the determination of CVL in similar pharmaceutical dosage forms [3,18,19].…”
Section: High Pressure Liquid Chromatography (Hplc) Conditions and Asmentioning
confidence: 99%